Effects of using slurry ice on the microbiological, chemical and sensory assessments of aquacultured sea bass (Dicentrarchus labrax) stored at 4 degrees C - Kilinc, B; Cakli, S; Cadun, A; Tolasa, S (European Food Research and Technology, 2006)
WOS: 000233722100020 Slurry ice, a biphasic system consisting of small spherical ice crystals surrounded by seawater at subzero temperature, was evaluated as a new chilled storage method for whole sea bass (Dicentrarchus labrax) a sparidae fish species of remarkable commercial interests. Four different group of chilling methods were used in this study; in slurry ice packaged on board (group A), in slurry ice packaged on company after 2 h (group B), slurry + flake ice packaged on board (group C) and only flake ice packaged on board (group D). The effect of this advanced system at the beginning of storage on quality losses and the shelf-life of aquacultured sea bass was evaluated. Mesophilic counts for sea bass exceeded 7 log cfu/g, which is considered the maximum level for acceptability for freshwater and marine fish after 13 days for groups C and D, and 15 days for groups A and B. At day 15; total volatile basic nitrogen (TVB-N) values of groups A-D reached the legal limits (35 mg/100 g set for TVB-N) for consumption. According to the results of sensory analyses, up to day 11, all the groups were determined as 'acceptable' but on day 13, the groups A-D were no longer acceptable. The main negative aspect related to quality loss in slurry ice group corresponded to the appearance of eyes and gills. Using slurry ice at the beginning of packaging did not affect the shelf-life of sea bass stored at 4 degrees C.